2010
DOI: 10.1039/b923557d
|View full text |Cite
|
Sign up to set email alerts
|

Heterolytic H2 activation by rhodium thiolato complexes bearing the hydrotris(pyrazolyl)borato ligand and application to catalytic hydrogenation under mild conditions

Abstract: Thiolato complexes of Rh(III) bearing a hydrotris(3,5-dimethylpyrazolyl)borato ligand (Tp(Me2)) have been prepared, and their reactivity toward H(2) has been investigated. The bis(thiolato) complex [Tp(Me2)Rh(SPh)(2)(MeCN)] (1) reacted with 1 atm H(2) at 20 degrees C to produce the hydrido-thiolato complex [Tp(Me2)RhH(SPh)(MeCN)] (2) and PhSH via heterolytic cleavage of H(2). This process is reversible and in equilibrium in THF and benzene. The bis(selenolato) complex [Tp(Me2)Rh(SePh)(2)(MeCN)] (4) was also co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 114 publications
0
42
0
Order By: Relevance
“…In 60, the bis( phenylselenolate)Rh(III) unit is coordinated with tris(3,5-dimethylpyrazol-1-yl)borate (Tp Me2 ) coligand resulting in [Tp Me2 Rh(SePh) 2 (MeCN)]. 110,111 Complex 60 has been used in catalytic hydrogenation. Reactions of the Rh(I) complex [Tp Me2 Rh(coe)(MeCN)] (coe = cyclooctene) with one equiv.…”
Section: Rhodium Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…In 60, the bis( phenylselenolate)Rh(III) unit is coordinated with tris(3,5-dimethylpyrazol-1-yl)borate (Tp Me2 ) coligand resulting in [Tp Me2 Rh(SePh) 2 (MeCN)]. 110,111 Complex 60 has been used in catalytic hydrogenation. Reactions of the Rh(I) complex [Tp Me2 Rh(coe)(MeCN)] (coe = cyclooctene) with one equiv.…”
Section: Rhodium Complexesmentioning
confidence: 99%
“…of diphenyldiselenide PhSeSePh afforded 60 (Scheme 7). [110][111][112][113] Chart 9 Methylselenolate bridged diruthenium complexes.…”
Section: Rhodium Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such H 2 activation by metalÀ thiolato complexes have been reported in literature. [33][34][35] Ohki et al [36] reported on the facile heterolysis of H 2 by Ir and Rh half-sandwich complexes for which a sulfur atom bonded to the metal served as a site for H 2 cleavage resulting in SÀ H and metal hydride groups. As such the structure of the resulting metal hydride obtained from 7 may exist as F (Scheme 3 cycle 1).…”
Section: Mechanism Of Action Of Bimetallic Complexes For Co 2 Hydrogenationmentioning
confidence: 99%
“…Transition metal complexes containing a coordinative unsaturated metal center and a Brønsted basic π-donor ligand have been reported in homogeneous transfer hydrogenation. Ligands with different transition metals such as amido [19][20][21][22], thiolate [23][24][25][26][27][28], phosphido [29], imido [30][31][32][33][34][35][36][37][38][39][40], oxo [41][42][43][44][45][46], and sulfido [47] have been investigated for this reaction. The most active and selective catalysts for the transfer hydrogenation reactions are ruthenium [48], iridium [49] and rhodium [50] complexes containing nitrogen, oxygen and N,O-donor ligands [51][52][53][54][55][56][57][58].…”
Section: Scheme 1 Hydrogen Transfer Reaction Of Ketones (Htr)mentioning
confidence: 99%